Decoding the influence of anticipatory states on visual perception in the presence of temporal distractors - Freek van Ede; Sammi R. Chekroud; Mark G. Stokes; Anna C. Nobre (Nature Communications, 2018)
Anticipation helps to prioritise the processing of task-relevant sensory targets over irrelevant distractors. Here the authors analyse visual EEG responses and show that anticipation may do so by enhancing the neural representation of the target and by delaying the interference caused by distractors that follow closely in time.